Successful desensitization to idursulfase in a patient with type II mucopolysaccharidosis (Hunter syndrome). (2011)
Hunter syndrome or type II mucopolysaccharidosis is a rare lysosomal storage disease of X-linked recessive inheritance. It is characterized by a lack of the enzyme iduronate 2 sulfatase (I2S), which leads to the accumulation of glycosaminoglycans in many cells and tissues, resulting in myocardiopathy, airway obstruction, skeletal deformities, and severe and progressive neurologic disturbances. Those affected often die in the second decade of life [1]. Until the appearance of enzyme replacement therapy, there were few therapeutic options that had a signifi cative impact on the natural course of the disease. Nowadays, however, it is possible to compensate for the enzymatic loss with idursulfase, a purifi ed form of I2S produced using DNA recombinant technology in a continuous human cell line [2]. However, the administration of idursulfase is associated with infusion-related hypersensitivity reactions in a high percentage of patients